Evaluation of a new brain tissue probe for cerebral blood flow monitoring in an experimental pig model - Seule, Martin; Isaak, Rimmon; Sánchez-Porras, Renán; Sakowitz, Oliver; Keller, Emanuela; Unterberg, Andreas; Orakcioglu, Berk (Neurosurgery, 2016)
Bedside monitoring of cerebral blood flow (CBF) may provide new insights into the pathophysiology of brain injury, allow early detection o
Gesehen am 05.05.2020